Studi Optimasi Waktu dan Biaya dengan Metode Time Cost Trade Off pada Proyek Konstruksi : Studi Kasus Proyek Jalan Bugel-Galur-Poncosari Cs. Tahap I, Provinsi D.I. Yogyakarta - Mandiyo Priyo; Sarwidi Sudiro (Universitas Muhammadiyah Yogyakarta, 2017)
The important things that neededto know when planning the construction project are to optimize the time and the cost. To set the good time and the good cost for the implementation will give benefit greatly or maximum and avoid the cost of penalties for project delays. It is necessary to optimize the time and cost with creating the networking, searching for critical activities, and also calculate the duration of the project implementation and a number of resources. The purposes of this research are to know the changes in cost and time of the project implementation with a variety of additional work hours, employers, and equipments, to know the changes in time and cost of the project implementation with the additional variety of equipments and employee, and to know the comparison between the penalty cost and the additional of work hours cost, the additional of equipment cost, and also the additional of employs. The data used in this study is from the road construction project data of Bugel-GalurPoncosari Cs (Stage I). The data analysis of this research uses Microsoft Project 2010 and the method is time cost trade off. The critical path and the cost increase due to work hours additional obtain from the computer analysis of Microsoft project 2010, also the acceleration duration and cost increases due to the duration acceleration of the results obtains from the analysis method of time cost trade off. The results of this study are (1) the time and cost of the project in normal conditions with duration of 177 days and a cost of Rp 40,897,811,578.00, additional 1 hour of additional work hours obtains from crashing duration of 110.03 days, the cost is Rp 40,076,775,588.21. The addition of 2 hours additional work hours obtains from crashing duration of 62.1 days, the cost is Rp 39,633,316,095.13. The addition of 3 hours additional work hours obtains from crashing duration of 26.89 days, the cost is Rp 39,369,085,607.83. (2) The addition of equipment and employers using a duration of 1 hour additional work hours with a duration of crashing of 110.03 days, the cost is Rp 39,931,863,398.85. The addition of equipment and employers with duration of 2 hours additional work hours crashing duration of 62.1 days, the cost is Rp39,240,658,440.70. The addition of equipment and employers with duration of 3 hours additional work hours crashing duration of 26.89 days, the cost is Rp 38,733,785,415.45. (3) To accelerate the duration of the project cost with the addition of equipment and employers is efficient and cheap when compared to the addition of work hours, and also cheaper than the costs incurred if the project has been delayed and subject fined.